Organization of Islamic Education Marketing Services at the MTs Negeri 4 Musi Banyuasin - Adhelmi; Zainal Berlian; Ahmad Zainuri (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2024)
This study aims to analyze the organization of Islamic education marketing services at MTs Negeri 4 Musi Banyuasin. The method used in writing this article is a literature study or literature research by managing and analyzing reference sources from articles, journals, and other sources from the internet. The results of the study show that the organizational structure of educational marketing at MTs Negeri 4 Musi Banyuasin heavily relies on cooperation between various parties in the madrasa. Each part has its own duties and roles that support each other in achieving marketing goals, which are to increase the number of new student registrations and introduce the advantages of MTs Negeri 4 Musi Banyuasin to the community. With a clear structure and good coordination, educational marketing at MTs can run effectively and efficiently.